Co / TiO2-CNTs catalyst, preparation method and application
By preparing Co/TiO2-CNTs catalysts, the porosity and absorption rate of the catalyst are expanded by carbon nanotubes, the problems of high-temperature demand and low-carbon conversion in bio-oil reforming are solved, and high-efficiency hydrogen yield and carbon conversion rate under low temperature conditions are achieved.
Patent Information
- Application Number
- CN202411965203.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
AI Technical Summary
Bio-oils face problems of high temperature demand and low carbon conversion during reforming. The existing catalysts have poor catalytic effects at low temperatures, resulting in low hydrogen yield and carbon conversion.
The Co/TiO2-CNTs catalyst was used, which prepared the TiO2-CNTs support by the sol-gel method, and cobalt elements were added by the impregnation method to form the Co/TiO2-CNTs catalyst. The addition of carbon nanotubes expands the porosity and visible light absorption of the catalyst and improves the catalytic activity.
Under low temperature conditions, the hydrogen yield and carbon conversion rate of bio-oil are significantly improved, the carbon emissions during the reforming process are reduced, and the requirements of sustainable development are met.
Smart Images

Figure CN119793462A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bio-oil reforming catalysts, and in particular to a Co / TiO2-CNTs catalyst, a preparation method and application thereof. Background Art
[0002] With the acceleration of industrialization and urbanization, climate change and energy shortage are becoming increasingly prominent. The depletion of traditional energy can no longer meet the needs of rapid and sustainable economic and social development. Exploring and developing renewable green energy that can replace traditional fossil energy is of great significance to alleviating energy shortages and ecological environmental pollution. Hydrogen energy is a clean, renewable energy that is non-toxic, storable and transportable. At present, efficient hydrogen production has become a common concern of scientists around the world. Bio-oil, as a renewable biomass resource, may become an important source of hydrogen production. Acetic acid, ethanol, etc. are one of the main components of bio-oil and are also model compounds for studying bio-oil steam reforming. Bio-oil single thermal catalytic reforming hydrogen production usually faces the problems of high reforming temperature and low carbon conversion rate. The photothermal synergistic catalytic reforming of bio-oil to produce hydrogen is expected to improve the carbon conversion rate and hydrogen production rate of bio-oil steam reforming under low temperature and low carbon emission conditions. This technology meets the requirements of sustainable development and environmental friendliness and has important application prospects in the field of energy conversion.
[0003] At present, the catalysts used for reforming bio-oil are mainly industrial nickel-based catalysts, etc. These catalysts can only play a better catalytic effect at high temperatures. Therefore, in order to obtain a higher hydrogen yield, it is usually necessary to increase the reforming temperature. Bio-oil is composed of a variety of organic compounds, including fatty acids, esters, phenols, etc., and the thermal stability and reactivity of these compounds vary. During the reforming process, some compounds are difficult to completely convert at low temperatures, resulting in low carbon conversion rate.
[0004] TiO2 has good photocatalytic properties. In addition, it is widely used in the field of photocatalysis due to its low price, stable chemical properties and good biocompatibility. However, due to the wide band gap, most of the photogenerated electron holes are easily recombined in the catalyst body, resulting in low photocatalytic activity. Summary of the invention
[0005] The purpose of the present invention is to provide a bio-oil photothermal reforming catalyst Co / TiO2-CNTs that can improve hydrogen yield and carbon conversion rate; another purpose of the present invention is to provide a method for preparing the Co / TiO2-CNTs catalyst.
[0006] The present invention discloses a method for preparing a Co / TiO2-CNTs catalyst, comprising the following steps:
[0007] S1 Preparation of TiO2-CNTs carrier: C 16H 36 O4Ti (tetrabutyl titanate) and an organic solvent are mixed uniformly to form a solution; carboxylated carbon nanotubes, an organic solvent and an inhibitor are mixed to form a suspension; the temperature of the solution is controlled at 0-6°C, and the suspension is added dropwise; after the suspension is added dropwise, the temperature is raised and stirred to form a gel; the gel is dried and calcined for the first time to obtain a TiO2-CNTs carrier;
[0008] S2 Preparation of Co / TiO2-CNTs: The TiO2-CNTs carrier is mixed with an aqueous solution containing cobalt, heated to remove water, and the obtained solid is calcined for a second time and ground into powder.
[0009] The addition of carbon nanotubes (CNTs) during the preparation of the catalyst has the effect of expanding the pores of the catalyst and increasing the absorption rate of visible light.
[0010] Furthermore, in step S1, the organic solvent includes one or more of ethanol, n-butanol, isobutanol, and ethylene glycol; the mass of the organic solvent added is 16 H 36 The mass ratio of O4Ti added is 1-2:1.
[0011] Controlling the amount of organic solvent added within this range can regulate the gelation speed. If the amount is greater than this range, the gelation rate will be too slow.
[0012] Furthermore, in step S1, the inhibitor includes acetic acid; the added volume of the acetic acid is equal to the volume of the C 16 H 36 The volume ratio of O4Ti is 0.2-0.5.
[0013] Acetic acid is added as an inhibitor to control the reaction rate. The amount of acetic acid added should not be too much, otherwise the reaction will not form a gel.
[0014] Furthermore, in step S1, the pH of the suspension is adjusted to 1.5-2.5 by nitric acid.
[0015] Nitric acid is added to adjust the pH so that tetrabutyl titanate is hydrolyzed at a certain pH value.
[0016] Furthermore, in step S1, the carbon nanotubes are carboxylated carbon nanotubes; the molar number of the carboxylated carbon nanotubes added is the same as that of the C 16 H 36 The molar ratio of O4Ti added is 7-60%.
[0017] The surface of carboxylated carbon nanotubes has a large number of oxygen-containing groups, which can provide a large number of nucleation sites for the in-situ growth of TiO2 nanoparticles and improve the utilization rate of TiO2 for ultraviolet light.
[0018] Furthermore, in step S1, the temperature is raised to 30-50° C. with stirring, and the mixture is stirred until a gelation reaction occurs to form a gel that does not flow along the inclined beaker wall; and the obtained gel is then dried at 70-90° C. for 10-24 hours.
[0019] Furthermore, in step S1, the control conditions of the first calcination are: in an atmosphere of nitrogen and air, wherein the volume ratio of nitrogen to air is 10-80%, the temperature is raised to 400-500° C. at a rate of 2-5° C. / min, and calcined for 2-4 hours.
[0020] By controlling the calcination temperature, some carbon nanotubes remain in the catalyst, while another part of the carbon nanotubes is converted into carbon dioxide during the calcination process, thereby forming new pores, increasing the specific surface area and porosity of the catalyst, and playing the role of pore expansion.
[0021] Furthermore, in the step S2, the ratio of the mass of the cobalt element to the mass of the TiO2-CNTs carrier is 5-20%; the control conditions of the second calcination are: under normal pressure, in an air atmosphere, heating to 400-500° C., and calcining for 2-4 hours.
[0022] The present invention also provides a Co / TiO2-CNTs catalyst, which is prepared by the preparation method described above and has a specific surface area of 16-100m 2 / g; pore volume is 0.033-0.1cm 3 / g; average pore diameter 3-10nm.
[0023] Furthermore, the specific surface area of Co / TiO2-CNTs catalyst is 16-41m 2 / g; pore volume is 0.033-0.093cm 3 / g; average pore diameter 4.6-6.8nm.
[0024] The present invention also provides an application of a Co / TiO2-CNTs catalyst, such as the Co / TiO2-CNTs catalyst described above is applied to bio-oil reforming to produce hydrogen.
[0025] The present invention provides a Co / TiO2-CNTs catalyst, in which carbon nanotubes are added during the preparation process. The carbon nanotubes have the advantages of high conductivity, large specific surface area, high chemical stability, etc. Combining the carbon nanotubes with TiO2 is beneficial to increasing the specific surface area and active sites of TiO2, slowing down the rate of recombination of TiO2 electron-hole pairs, extending the life of photogenerated carriers, reducing the recombination probability of TiO2 photogenerated carriers, improving its quantum efficiency, and improving the efficiency of photocatalytic reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is a scanning electron microscope image of the TiO2-CNTs (60%) carrier of Example 3 of the present invention;
[0027] Figure 2 is a scanning electron microscope image of Co / TiO2-CNTs (60%) of Example 3 of the present invention;
[0028] Figure 3 It is the XRD spectrum of the catalysts prepared in Examples 1-3 and Comparative Example 1 of the present invention;
[0029] Figure 4 It is the UV-visible absorption spectrum of the catalysts prepared in Examples 1-3 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0030] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0031] The carbon nanotubes used in this embodiment are carboxylated carbon nanotubes (CNTs-COOH) purchased from Jiangsu Pioneer Nanomaterials Technology Co., Ltd. The inner diameter is 5-10 nm, the outer diameter is 10-20 nm, and the carboxyl content is about 2%.
[0032] Example 1
[0033] S1 Preparation of TiO2-CNTs carrier:
[0034] Add 50ml C 16 H 36 O4Ti (density of tetrabutyl titanate is 0.98 g / ml) was dissolved in 80 ml of CH3CH2OH (anhydrous ethanol), and then placed in an ice water bath and stirred rapidly to form a solution.
[0035] 0.12 g of CNTs (carbon nanotubes) was added to 60 ml of CH3CH2OH, and then 20 ml of deionized water and 20 ml of acetic acid were added, and the mixture was stirred rapidly. During the mixing process, a small amount of HNO3 (concentration 20%) was added dropwise until pH = 2, and then ultrasonic vibration was applied for 10 min.
[0036] The mixed solution containing CNTs was added dropwise to the C in the ice water bath at a rate of 3 ml / min by a peristaltic pump. 16 H 36 The O4Ti solution was stirred continuously during the dropwise addition process to prevent it from solidifying too quickly.
[0037] After the addition was complete, the temperature of the reactants was raised to 40°C and stirring was continued until a gelation reaction occurred to form a black sol that would not flow along the wall of the inclined beaker, and then the obtained gel was dried at 90°C for 12 h.
[0038] The dried gel was placed in an atmosphere furnace, heated to 450° C. at a rate of 3° C. / min in a nitrogen / air (45% by volume) atmosphere, and calcined at 450° C. for 3 h to obtain a TiO2-CNTs carrier.
[0039] Preparation of Co / TiO2-CNTs by S2:
[0040] Weigh 4.94g of Co(NO3)2·6H2O and dissolve it in deionized water. Add 10g of the prepared TiO2-CNTs carrier powder to a cobalt nitrate aqueous solution (the ratio of the mass of the cobalt element to the mass of the TiO2-CNTs carrier is 10%) and stir continuously for 2 hours using a magnetic stirrer. Then transfer the suspension to a constant temperature water bath at 90°C to evaporate the water completely. Then put the obtained material into an oven and dry it for 12 hours. Then put it into a normal pressure furnace and calcine it continuously for 3 hours in an atmosphere of air at 450°C. Finally, grind the sample to 40-60 mesh to obtain Co / TiO2-CNTs (7%). The molar number of carbon nanotubes added is the same as that of the C 16 H 36 The molar ratio of O4Ti added is 7%.
[0041] The TiO2-CNTs carrier was prepared by a sol-gel method, and the Co / TiO2-CNTs catalyst was prepared by an impregnation method.
[0042] Example 2
[0043] The difference between Example 2 and Example 1 is that the mass of CNTs (carbon nanotubes) added in step S1 is 0.34 g. The molar number of carbon nanotubes added is the same as that of the CNTs (carbon nanotubes) added in step S1. 16 H 36 The molar ratio of O4Ti added is 20%, and the obtained catalyst is Co / TiO2-CNTs (20%).
[0044] Example 3
[0045] The difference between Example 3 and Example 1 is that the mass of CNTs (carbon nanotubes) added in step S1 is 1.03 g. The molar number of carbon nanotubes added is the same as that of the CNTs (carbon nanotubes) added in step S1. 16 H 36 The molar ratio of O4Ti added is 60%, and the obtained catalyst is Co / TiO2-CNTs (60%).
[0046] The TiO2-CNTs (60%) carrier and Co / TiO2-CNTs (60%) catalyst prepared in Example 3 were subjected to morphological characterization analysis using a scanning electron microscope.
[0047] like Figure 1 As shown in the figure, the carrier TiO2-CNTs (60%) contains a large number of carbon nanotube fibers with a diameter of about 20nm. The TiO2 prepared by the sol-gel method is aggregated on the surface of the carbon nanotubes, with a small particle size, and some agglomeration occurs. When the active metal Co is loaded, the carbon nanotube fibers in the Co / TiO2-CNTs (60%) catalyst disappear. This may be due to the fact that some carbon nanotube fibers are oxidized and broken after the impregnation and calcination procedures during the Co loading preparation process. Figure 2 As shown in Figure 2, new pores were formed in the TiO2-CNTs (60%) catalyst during the oxidative calcination process, such as Figure 2 As shown in the dashed box, this can also be confirmed from the BET results below. After adding CNTs, the specific surface area and porosity of the catalyst are greatly increased, and the addition of CNTs achieves the effect of pore expansion. This is because part of the carbon nanotubes are burned during calcination, achieving the pore expansion effect.
[0048] Comparative Example 1
[0049] Preparation of TiO2 carrier. The preparation of TiO2 is based on C 16 H 36 O4Ti is the precursor, CH3CH2OH is the solvent, and the specific steps are as follows:
[0050] Measure 50ml C 16 H 36 O4Ti was slowly dripped into 80 ml of anhydrous ethanol and stirred vigorously with a magnetic stirrer for 10 min to form a yellow clear solution A;
[0051] Add 20 ml of acetic acid and 20 ml of deionized water to 80 ml of anhydrous ethanol and stir vigorously to obtain a clear solution B. During the stirring process, add an appropriate amount of HNO3 to solution B to adjust the pH to 2.
[0052] Use a peristaltic pump to slowly drip solution B into solution A (under an ice-water bath) at a rate of about 3 ml / min, and a light yellow solution is obtained after the dripping is completed. Heat the temperature of the light yellow solution to 40°C in a water bath, and continue stirring until a gelation reaction occurs to form a white gel. When the beaker is tilted, the gel will not flow along the wall of the cup. Dry the obtained gel at 90°C for 12 hours to obtain yellow crystals, which are then ground to obtain light yellow powder. Put it into an air atmosphere furnace, heat it to 500°C at a heating rate of 3°C per minute, and continue calcining for 3 hours to obtain a TiO2 carrier.
[0053] Weigh 4.94g of Co(NO3)2·6H2O and dissolve it in deionized water. Add 10g of the prepared TiO2 carrier powder into a cobalt nitrate aqueous solution (the ratio of the mass of the cobalt element to the mass of the TiO2 carrier is 10%), and stir continuously for 2 hours using a magnetic stirrer. Then transfer the suspension to a 90°C constant temperature water bath to completely evaporate the water. Then put the obtained material into an oven and dry it for 12 hours. Then put it into a normal pressure furnace and calcine it continuously for 3 hours in an atmosphere of 450°C air. Finally, grind the sample to 40-60 mesh to obtain a Co / TiO2 catalyst.
[0054] Performance testing and result analysis:
[0055] The catalysts and carbon nanotubes prepared in Examples 1-3 and Comparative Example 1 were subjected to XRD tests. The test results are as follows: Figure 3 shown.
[0056] like Figure 3 As shown, the catalysts obtained in Examples 1-3 and Comparative Example 1 have characteristic diffraction peaks of TiO2 and Co3O4. The grain size of the XRD sample Co3O4 was calculated by the Scherrer formula, D = Kγ / (βcosθ), where K is a constant; γ is the wavelength of the X-ray; β is the half-height width of the diffraction peak; θ is the diffraction angle. The value of the constant K is related to the definition of β. When β is the half-width height, K is 0.89; when B is the integral width, K is 1.0. The calculation results are shown in Table 1.
[0057] Examples 1-3 and Comparative Example 1 were subjected to BET tests, and the results obtained are shown in Table 1.
[0058] Table 1 Physical and chemical properties of the catalysts prepared in Examples 1-3 and Comparative Example 1
[0059] catalyst <![CDATA[S Bet m 2 / g]]> <![CDATA[V pore cm 3 / g]]> <![CDATA[D pore nm]]> <![CDATA[d(Co3O4) a nm]]> Comparative Example 1 2.29 0.010 15.908 35 Example 1 16.64 0.033 4.693 34 Example 2 20.53 0.035 5.344 24.6 Example 3 41.48 0.093 6.790 17.1
[0060] a According to XRD
[0061] As shown in Table 1, compared with Comparative Example 1, the specific surface area, pore volume and pore diameter of the catalysts prepared in Examples 1-3 are significantly larger than those of the catalyst prepared in Comparative Example 1, which fully proves that adding carbon nanotubes during the preparation process can greatly increase the specific surface area and porosity of the catalyst.
[0062] The catalysts obtained in Examples 1-3 and Comparative Example 1 were tested for full-band absorption spectra in the wavelength range of 200-780 nm. The test results are as follows: Figure 4 shown.
[0063] like Figure 4As shown, the catalysts obtained in Examples 1-3 and Comparative Example 1 are all in a reduced state. Compared with Comparative Example 1, the absorbance of Examples 1-3 doped with carbon nanotubes increased significantly, and the addition of carbon nanotubes significantly increased the absorbance of the catalyst. The absorbance of the catalysts of Examples 1-3 first increased with the increase of wavelength, and then the absorbance decreased slightly in the wavelength range of 320nm to 380nm, among which the decrease in Example 3 was the largest. In the visible light band, the absorbance of the catalysts of Examples 1-3 gradually increased with the increase of the amount of carbon nanotubes added, and the absorbance of the catalysts of Examples 2 and 3 was almost the same. In the ultraviolet band, the absorbance of the catalyst of Example 1 was lower than that of the catalyst of Example 3. In this embodiment, a xenon lamp was used as the light source. The energy of the xenon lamp light source in the ultraviolet region is less, and the main light intensity is concentrated in the visible light region, so the absorbance of Example 3 and Example 2 is equivalent.
[0064] Bio-oil photothermal catalytic reforming experiment:
[0065] Bio-oil is the product of rapid thermal cracking of biomass. It is a complex organic mixture with a variety of components, mainly including acids, aldehydes, alcohols, esters, ketones, phenols and sugars, with an estimated number of more than 100 substances.
[0066] This patent uses acids and alcohols with high bio-oil content as bio-oil model materials to carry out experiments, with the proportions being 10-80wt% acetic acid, 10%-40wt% methanol, and 10-40wt% ethanol.
[0067] Experimental conditions: under normal pressure, the bio-oil model (molar number of water / bio-oil model = 5-10) is fed into a vaporizer through a feed pump, the vaporization temperature is 150°C, and then mixed with nitrogen and flows into a reactor. The reactor is heated and temperature-controlled by an electric heating furnace, and the catalysts of Examples 1-3 and Comparative Example 1 are used respectively (the catalyst reaction tube is a quartz tube, which does not affect the illumination of the xenon lamp) to complete the thermal catalytic reaction or the photothermal synergistic catalytic reaction, wherein the light source is a xenon lamp (Microsolar 300, Perfect Light, equipped with a Visref filter, the wavelength output range is 320-780nm, the total radiation energy of the bulb is 50W, the output power in the ultraviolet light region with a wavelength less than 390nm is 2.6W, and the output power in the visible light region with a wavelength of 390-770nm is 19.6W), and then flows into a gas-liquid separator, the gas is detected and analyzed online, and the liquid is collected and detected. The gaseous products include H2, CO, CO2, CH4, etc. The reactor temperature is adjusted to 350°C, 400°C, 450°C, and 500°C. The hydrogen yield and carbon conversion rate are calculated. The results are shown in Tables 2 and 3.
[0068] The indicators for evaluating catalyst performance include hydrogen yield (Y H2 ) and carbon conversion rate (XC ), the calculation formula is as follows:
[0069]
[0070] The hydrogen production rate increase is defined as:
[0071]
[0072] Table 2 Test results of hydrogen production rate and hydrogen improvement rate of comparative examples and embodiments
[0073]
[0074] As shown in Table 2, when thermal catalysis is performed alone at 500°C, the hydrogen yields of Examples 1-3 are significantly improved compared with the hydrogen yield of Comparative Example 1. In the temperature range of 450-500°C for photothermal synergistic catalysis, the hydrogen yields of Examples 1-3 are significantly increased compared with Comparative Example 1. At 500°C, the hydrogen yield of Comparative Example 1 is only 68.55%, but that of Examples 1-3 is 100%.
[0075] Table 3 Test results of carbon conversion rate and carbon conversion rate improvement rate of comparative examples and embodiments
[0076]
[0077]
[0078] As shown in Table 3, when thermal catalysis is performed alone at 500°C, the carbon conversion rate of Examples 1-3 can reach 100%, while that of the comparative example is only 82.44%. The carbon conversion rate of Comparative Example 1 is also higher than that of thermal catalysis alone during photothermal catalysis, but the carbon conversion rate of Examples 1-3 is higher, reaching 96.66-100% at 450°C, thus proving that the addition of carbon nanotubes during preparation helps improve the catalytic performance of Co / TiO2 catalysts.
[0079] Compared with Comparative Example 1, the hydrogen yield of Examples 1-3 at 450-500° C. is significantly improved, and is as high as about 100% at 500° C. Compared with Comparative Example 1, the carbon conversion rate of Examples 1-3 at 450-500° C. is significantly improved, and is as high as about 100% at 450-500° C.
[0080] Compared with Comparative Example 1, the catalytic effects of the catalysts of Examples 1-3 are more excellent under both thermal catalysis and photothermal synergistic catalysis conditions.
[0081] Meanwhile, by comparison with Examples 1-3, the catalyst activity of Co / TiO2-CNTs (20%) prepared in Example 2 is the best. Under photocatalysis at 450° C., the carbon conversion rate reaches 100% and the hydrogen yield reaches 80%.
[0082] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a Co / TiO2-CNTs catalyst, characterized in that: The following steps are involved: S1 Preparation of TiO2-CNTs carrier: C 16 H 36 O4Ti and an organic solvent are mixed evenly to form a solution; carbon nanotubes, an organic solvent and an inhibitor are mixed to form a suspension; the temperature of the solution is controlled at 0-6°C and the suspension is added dropwise; after the suspension is added dropwise, the temperature is raised and stirred to form a gel; the gel is dried and calcined for the first time to obtain a TiO2-CNTs carrier; S2 Preparation of Co / TiO2-CNTs: The TiO2-CNTs carrier is mixed with an aqueous solution containing cobalt, heated to remove water, and the obtained solid is calcined for a second time and ground into powder.
2. The method for preparing a Co / TiO2-CNTs catalyst according to claim 1, characterized in that: In step S1, the organic solvent includes one or more of ethanol, n-butanol, isobutanol, and ethylene glycol; the mass of the organic solvent added is 16 H 36 The mass ratio of O4Ti added is 1-2:
1.
3. The method for preparing a Co / TiO2-CNTs catalyst according to claim 1, characterized in that: In step S1, the inhibitor includes acetic acid; the volume of the added acetic acid is about the same as that of the C 16 H 36 The volume ratio of O4Ti is 0.2-0.
5.
4. The method for preparing a Co / TiO2-CNTs catalyst according to claim 1, characterized in that: In the step S1, the pH of the suspension is adjusted to 1.5-2.5 by nitric acid.
5. The method for preparing a Co / TiO2-CNTs catalyst according to claim 1, characterized in that: In step S1, the carbon nanotubes are carboxylated carbon nanotubes; the molar number of the carboxylated carbon nanotubes added is equal to the molar number of the C 16 H 36 The molar ratio of O4Ti added is 7-60%.
6. The method for preparing a Co / TiO2-CNTs catalyst according to claim 1, characterized in that: In the step S1, the temperature is raised to 30-50° C. and stirred until a gelation reaction occurs to form a gel that does not flow along the inclined beaker wall; and then the obtained gel is dried at a temperature of 70-90° C. for 10-24 hours.
7. The method for preparing a Co / TiO2-CNTs catalyst according to claim 6, characterized in that: In the step S1, the control conditions of the first calcination are: in an atmosphere of nitrogen and air, wherein the volume ratio of nitrogen to air is 10-80%, the temperature is raised to 400-500° C. at a rate of 2-5° C. / min, and calcined for 2-4 hours.
8. The method for preparing a Co / TiO2-CNTs catalyst according to claim 1, characterized in that: In the step S2, the ratio of the mass of the cobalt element to the mass of the TiO2-CNTs carrier is 5-20%; the control conditions of the second calcination are: under normal pressure, in an air atmosphere, heating to 400-500° C., and calcining for 2-4 hours.
9. A Co / TiO2-CNTs catalyst, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8, the specific surface area is 16-100m 2 / g; The pore volume is 0.033-0.1cm 3 / g; average pore diameter 3-10nm.
10. An application of Co / TiO2-CNTs catalyst, characterized in that: The Co / TiO2-CNTs catalyst as described in claim 9 is used for bio-oil reforming to produce hydrogen.